2011
DOI: 10.1007/s00027-011-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning effects of intermittent stream flow on leaf litter decomposition

Abstract: Autumnal input of leaf litter is a pivotal energy source in most headwater streams. In temporary streams, however, water stress may lead to a seasonal shift in leaf abscission. Leaves accumulate at the surface of the dry streambed or in residual pools and are subject to physicochemical preconditioning before decomposition starts after flow recovery. In this study, we experimentally tested the effect of photodegradation on sunlit streambeds and anaerobic fermentation in anoxic pools on leaf decomposition during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…As intermittence metrics (e.g., drying duration, drying frequency) appear to be relatively good predictors for some important ecosystem processes and biodiversity patterns (e.g., Dieter et al 2011;Corti et al 2011;Datry et al 2011, Fritz andFeminella 2011;Von Schiller et al 2011), we suggest that scientists accumulate more univariate intermittence-ecology relationships across a wide range of temporary rivers in order to test for transferability and ubiquity among catchments in these relationships. Also, most extant bioindicators have little chance to succeed in detecting anthropogenic influences on temporary rivers because of the overwhelming effects of flow intermittence on biotic communities.…”
Section: Research Perspectives: Gaps and Needs In Temporary River Ecomentioning
confidence: 84%
See 3 more Smart Citations
“…As intermittence metrics (e.g., drying duration, drying frequency) appear to be relatively good predictors for some important ecosystem processes and biodiversity patterns (e.g., Dieter et al 2011;Corti et al 2011;Datry et al 2011, Fritz andFeminella 2011;Von Schiller et al 2011), we suggest that scientists accumulate more univariate intermittence-ecology relationships across a wide range of temporary rivers in order to test for transferability and ubiquity among catchments in these relationships. Also, most extant bioindicators have little chance to succeed in detecting anthropogenic influences on temporary rivers because of the overwhelming effects of flow intermittence on biotic communities.…”
Section: Research Perspectives: Gaps and Needs In Temporary River Ecomentioning
confidence: 84%
“…Another study included here (Dieter et al 2011) demonstrates that leaf litter decomposition is strongly influenced by repeated cessations of flow in temporary rivers. They found that leaf litter collected from either the dry streambed or from remnant pools were preconditioned to decomposition by UV radiation or wet-anoxic conditions, respectively.…”
Section: Scope Of the Special Issuementioning
confidence: 85%
See 2 more Smart Citations
“…In NPRS, coarse particulate organic matter (CPOM) accumulates in standing pools and at the surface of dry habitats, and as the river dries, the primary agents of CPOM decomposition shift from leaching and processing by aquatic micro-organisms and invertebrates to photo-degradation by UV and processing by terrestrial micro-organisms and invertebrates (Corti et al, 2011;Dieter et al, 2011). The decomposition rate decreases according to drying duration and the progressive disappearance and inactivity of aquatic fungi and shredders (e.g.…”
Section: Biogeochemical Processesmentioning
confidence: 99%